2013
DOI: 10.1063/1.4818495
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption properties of helical carbon nanofibers-coated carbon fibers

Abstract: Helical carbon nanofibers (HCNFs) coated-carbon fibers (CFs) were fabricated by catalytic chemical vapor deposition method. TEM and Raman spectroscopy characterizations indicate that the graphitic layers of the HCNFs changed from disorder to order after high temperature annealing. The electromagnetic parameters and microwave absorption properties were measured at 2–18 GHz. The maximum reflection loss is 32 dB at 9 GHz and the widest bandwidth under −10 dB is 9.8 GHz from 8.2 to 18 GHz for the unannealed HCNFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The moderate graphitization degree or proper content of defects for carbon-based materials has been confi rmed to be helpful for the attenuation of incident EM waves, because it could not only improve the matched characteristic impedance and prompt energy transition from contiguous states to Fermi level, but also introduce defect polarization relaxation and dipole relaxation. [ 8,15,43 ] In general, microwave absorption properties of an absorber are highly dependent on its EM parameters, including complex permittivity ( ε r = ε ′−j ε″ ) and complex permeability ( µ r = µ ′−j µ″ ), where the real parts of complex permittivity ( ε ′) and complex permeability ( µ ′) represent the storage capability of electric and magnetic energy, and imaginary parts ( ε″ and µ″ ) represent the loss capability of electric and magnetic energy. [ 44,45 ] Figure 3 a,b show the complex permittivity, including real parts ( ε′ ) and imaginary parts ( ε″ ), of rGO, ACMs, and rGO/ACMs/rGO in the range of 2.0-18.0 GHz.…”
Section: Resultsmentioning
confidence: 99%
“…The moderate graphitization degree or proper content of defects for carbon-based materials has been confi rmed to be helpful for the attenuation of incident EM waves, because it could not only improve the matched characteristic impedance and prompt energy transition from contiguous states to Fermi level, but also introduce defect polarization relaxation and dipole relaxation. [ 8,15,43 ] In general, microwave absorption properties of an absorber are highly dependent on its EM parameters, including complex permittivity ( ε r = ε ′−j ε″ ) and complex permeability ( µ r = µ ′−j µ″ ), where the real parts of complex permittivity ( ε ′) and complex permeability ( µ ′) represent the storage capability of electric and magnetic energy, and imaginary parts ( ε″ and µ″ ) represent the loss capability of electric and magnetic energy. [ 44,45 ] Figure 3 a,b show the complex permittivity, including real parts ( ε′ ) and imaginary parts ( ε″ ), of rGO, ACMs, and rGO/ACMs/rGO in the range of 2.0-18.0 GHz.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the composite method is another effective way to improve microwave absorption properties. 39 The combination of the two approaches might be a potential researching design in the field of EM wave absorbers. In addition, compared with the original helical nanofiber and HCNFs, we have studied the RL performance of straight fibers including straight original nanofibers and straight carbon fibers.…”
Section: View Article Onlinementioning
confidence: 99%
“…Helical CNF-coated carbon fiber is an efficient material for microwave absorbers due to its chemical stability, low density and broad absorption characteristics. 64 Lightweight magnetic composites of glass-iron-carbon exhibit good microwave absorption over a wide frequency band. 65 Hong et al investigated microwave absorption properties of titanium carbonitride and found that thin microwave absorbers can be realized by optimal doping of carbon in the compound.…”
Section: Microwave Absorbersmentioning
confidence: 99%
“…Table IV gives a clear picture of different microwave-absorbing materials that have been discussed in this paper and their absorption characteristics. 64 8.2-18 2.5 Titanium carbonitride (TiN 0:2 C 0:8 ) 66 11.1-13.6 1.32 40 wt.% Silica-Ni-C composite Shelly hollow microspheres 67 5.7-18 2.4-4 2 wt.% CNT/rice husk ash composite 127 12.48-16.47 2 40 wt.% Rice husk/nontoxic glue binder 139 6.3-7.1 37.5 ( # pyrolysis temperature, *À20 dB absorption frequency bandwidth).…”
Section: Other Important Materialsmentioning
confidence: 99%